Processus d’évaluation des incidences de la gouvernance des ressources naturelles par la méthode « matrice d’influence » au Burundi et Sud Kivu. - Serge Ngendakumana; P. Van Damme; Sylvain Mapatano; Deogratias Niyonkuru; Pascal Sanginga; Mwapu Isumbisho (VertigO, 2013)
Development stands as a result of changes in the people’s behavior and research plays the role of development catalyst. However, the conceptualization and methodology of action remain a challenge in the process of transforming lives and landscapes in the target areas. Hence, the question is: what is the best approach to evaluate projects and research programs in Africa to get the best lessons from interactive governance processes triggered within implementing organizations? This study uses outcome mapping tools to develop principles for assessing local governance processes based on multi-stakeholder focus group discussions, interactions with experts, as well as field observations conducted from May to July 2012 in the highlands of Burundi and South Kivu in DR Congo. The process has been described and tested in six sites covering two countries. It appears that the developed methological principles could help identify clearly the impact based on selected socio-environmental variables and perceived farmers’ constraints within collective governance initiatives implemented on the ground in the domain of natural resources management. The designed approach could seemingly be applicable in similar NRM contexts across the tropics beyond the great lakes of Africa.